Cardamom agro-environmental interrelationships analysis in Indian cardamom hills - Murugan, Muthusamy; Kuruvila, Anil; Anandhi, Aavudai; Pooja, A.; Ashokkumar, Kaliyaperumal; Dhanya, M. K.; Subbiah, A.; Alagupalamuthirsolai, M.; Sritharan, N. (Frontiers in Climate, 2023)
The rainfall pattern seen in the Indian Cardamom Hills (ICH) has been extremely variable and complicated, with El Niño-Southern Oscillation (ENSO) playing a crucial role in shaping this pattern. In light of this, more investigation is required through improved statistical analysis. During the study period, there was greater variability in rainfall and the frequency of rainy days. About 2730 mm of rainfall was reported in 2018, while the lowest amount (1168.3 mm) was registered for 2016. The largest decrease in decadal rainfall (>65 mm) was given by the decade 1960-1969, followed by 1980-1989 (> 40 mm) and 2010-2019 (>10 mm). In the last 60 years of study, there has been a reduction of rainy days by five days in the last decade (2000–2009), but in the following decade (2010–2019), it registered an increasing trend, which is only slightly less than two days. The highest increase in decadal rainy days was observed for the 1970–1979 period. The smallest decadal increase was reported for the last decade (2010–2019). Total sunshine hours were the highest (1527.47) for the lowest rainfall year of 2016, while the lowest value (1279) was recorded for the highest rainfall year (2021). The rainfall characteristics of ICH are highly influenced by the global ENSO phenomenon, both positively and negatively, depending on the global El Nino and La Nina conditions. Correspondingly, below and above-average rainfall was recorded consecutively for 1963-1973, 2003-2016, and 1970-2002. Higher bright forenoon sun hours occurred only during SWM months, which also reported maximum disease intensity on cardamom. The year 2016 was regarded as a poorly distributed year, with the lowest rainfall and the highest bright afternoon sun hours during the winter and summer months (January-May). Over the last three decades, the production and productivity of cardamom have shown a steady increase along with the ongoing local climatic change. Many of our statistical tests resulted in important information in support of temporal climatic change and variability. Maintaining shade levels is essential to address the adverse effects of increasing surface air temperature coupled with the downward trend of the number of rainy days and elevated soil temperature levels.